Transformative adaptation and implications for transdisciplinary climate change research - Hellin, Jonathan; Amarnath, Giriraj; Challinor, Andrew J.; Fisher, Eleanor; Girvetz, Evan Hartunian; Guo, Zhe; Hodur, Janet; Loboguerrero Rodriguez, Ana María; Pacillo, Grazia; Rose, S.; Schuetz, Tonya; Valencia, L.; et al. (IOP Publishing, 2022)
The severity of the climate challenge requires a change in the climate response, from an incremental to a more far-reaching and radical transformative one. There is also a need to avoid maladaptation whereby responses to climate risk inadvertently reinforce vulnerability, exposure and risk for some sections of society. Innovative technological interventions are critical but enabling social, institutional and governance factors are the actual drivers of the transformative process. Bringing about this transformation requires inter- and transdisciplinary approaches, and the embracing of social equity. In this Perspective, we unpack what this means for agricultural research and, based on our collective experience, we map out a research agenda that weaves different research components into a holistic and transformative one. We do not offer best practice, but rather reflections on how agricultural research can more readily contribute to transformative adaptation, along with the personal and practical challenges of designing and implementing such an agenda.